Children with Cerebral Palsy can imagine actions like their normally developed peers - Galli, Jessica; Garofalo, Gioacchino; Brunetti, Sara; Loi, Erika; Portesi, Michela; Pelizzari, Giovanni; Rossi, Andrea; Fazzi, Elisa; Buccino, Giovanni (Frontiers in Neurology, 2022)
The present study aimed at assessing whether children with Cerebral Palsy (CP) can imagine object directed actions similarly to their normally developed peers. We asked children with CP (n = 12) and paired healthy controls (n = 12) to imagine in first person perspective eight daily actions, after observing them through videoclips presented on a computer screen. During motor imagery (MI) children were interrupted at a specific timepoint (e.g., at 2.5s) from the start. Two frames extracted from the videoclips were then presented on the screen. One of the two depicted the correct timepoint at which the imagined action was interrupted, while the other represented an earlier or later timepoint. Children had to respond by pressing the key associated to the correct frame. Children also underwent VMIQ-2 questionnaire. Both groups performed similarly in the questionnaire and in the requested task, where they showed the same error rate. Errors mainly concerned the later frame, suggesting a similar strategy to solve the task in the two groups. The results support the view that children with CP can imagine actions similarly to their normally developed peers. This encourages the use of MI as a rehabilitative tool in children with motor impairment.